Penerapan Metode Demonstrasi dan Drill pada Kegiatan Ekstrakurikuler Drum Band di SMA Pembangunan Laboratorium UNP - Aqil Athallah Ramsyah; Esy Maestro (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to describe how demonstration and drill methods are applied in the drum band extracurricular activity process at UNP Laboratory Development High School. This type of research is qualitative research that uses descriptive methods. The instrument for this research was the researcher himself and was assisted by supporting instruments such as stationery, camera and voice recorder. Data collection techniques in this research are observation, interviews, documentation and literature study. The technical steps of data analysis are collecting data, identifying data and drawing conclusions. The results of research on the application of demonstration and drill methods to extracurricular drum band at the UNP Development Laboratory High School show a significant increase in the technical skills and harmony of students who are members of the extracurricular drum band. The demonstration method proved effective in explaining basic techniques and fostering initial understanding, although some students required repeat demonstrations for more complex techniques. Repeated use of drills increases consistency and precision of play, although some students require additional practice to achieve consistency in advanced techniques. Overall, students were satisfied with the training methods applied, but students wanted more variety in training to maintain their motivation and interest.